Legal Emotions: An Ethnography of Distrust and Fear in the Arab Districts of an Israeli City. Issue 3 (22nd July 2013) - Pasquetti, Silvia
<x xml:space="preserve">Abstract</x> Recent sociolegal scholarship has explored the role of emotions in lawmaking and policymaking on security and crime issues. This article extends this approach to the relationship between law enforcement and affect by addressing the role of policing and security agencies in the (re)production of long‐term emotions, which bind a collective and fuel ethnonational division. An ethnography of the distinct emotional climate within the Arab districts of Lod, an Israeli city, shows that this climate is structured by two emotions: rampant distrust toward friends and neighbors, and intense fear of the Israeli authorities. This emotional climate is the product of the subterranean ties of Lod Palestinians with the Israeli security agencies as well as their experiences of the blurred line between state security and crime control enforcement. I embed the initial creation and relative stability of this emotional climate in the broader relationship between the Israeli state and its Palestinian citizens from 1948 to the present. The article concludes with a discussion of how the law enforcement's affective production has consequences for the salience and scope of citizenship and by arguing for a greater focus on the link between law enforcement, collective emotions, and processes of inclusion and exclusion.